2021
DOI: 10.3390/molecules26061674
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Sorption of 5-Fluorouracil and Methotrexate onto Soil–pH, Ionic Strength, and Co-Contaminant Influence

Abstract: Nowadays anticancer drugs (ADs), like other pharmaceuticals, are recognized as new emerging pollutants, meaning that they are not commonly monitored in the environment; however, they have great potential to enter the environment and cause adverse effects there. The current scientific literature highlights the problem of their presence in the aquatic environment by publishing more and more results on their analytics and ecotoxicological evaluation. In order to properly assess the risk associated with the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Besides these methodological constrains, the toxicity of 5-FU might also be influenced by the ionic strength of the standard medium, which can also explain the large variation in the response to this drug observed in our study (MBL; OECD 2011 ). Previous studies have reported that even slight changes in the pH (for instance of half unit, that may be a result of the addition of algae at the start of the assay and/or during the assay due to the algae own metabolism) may lead to the formation of different species of the same compound (Markiewicz et al 2021 ). In that same study (Markiewicz et al 2021 ), the authors studied the acid–base equilibrium of 5-FU along with another cytostatic drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides these methodological constrains, the toxicity of 5-FU might also be influenced by the ionic strength of the standard medium, which can also explain the large variation in the response to this drug observed in our study (MBL; OECD 2011 ). Previous studies have reported that even slight changes in the pH (for instance of half unit, that may be a result of the addition of algae at the start of the assay and/or during the assay due to the algae own metabolism) may lead to the formation of different species of the same compound (Markiewicz et al 2021 ). In that same study (Markiewicz et al 2021 ), the authors studied the acid–base equilibrium of 5-FU along with another cytostatic drug.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that even slight changes in the pH (for instance of half unit, that may be a result of the addition of algae at the start of the assay and/or during the assay due to the algae own metabolism) may lead to the formation of different species of the same compound (Markiewicz et al 2021 ). In that same study (Markiewicz et al 2021 ), the authors studied the acid–base equilibrium of 5-FU along with another cytostatic drug. They found that at a pH closer to 9, dianionic species of 5-FU started to be formed and become predominant from this pH onwards, whilst at lower pH (closer to 7), 5-FU exists mostly in neutral and monoanionic forms (Markiewicz et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation